Magnetic Holder for Grinding Machine for Angle Cutting - Ibrahim, Nur Irma; Mohd Faiz, Nur Sofurah (Research and Innovation in Technical and Vocational Education and Training, 2022)
Product cutting is one of the most important processes involved in the production of a product regardless of industry, private workshops or learning institutions. A good cutting process will result in a neat product that will work well. This is because every material that needs to be cut and prepared to produce a product needs to be in the right size and less error especially when making angular cuts. Failure to perform this deduction process will result in the disruption of the product. The purpose of this study was to design, develop and test the functionality of magnetic holder for grinder machine to angular cutting is developed to facilitate the process of making angular cutting of project material desired. This product is developed using the ADDIE model which consists of five phases namely analysis phase, product design phase, product development phase, product implementation phase and product evaluation phase. Magnetic holder for grinder machine for angular cutting is tested in terms of the permissibility of the holder to hold the project material to be cut, to test the permissibility of the workpiece holder and to test the functionality while carrying out the work of cutting the workpiece according to the size required. To test the feasibility of this product, three product experts have been selected to test the product to ensure it works properly and safely when using it. Run test were performed three times to obtain the average cutting size of the workpiece according to the required size.